Using smartphones in supply chains = Wykorzystanie smartfonów w łańcuchach dostaw - Szymczak, Maciej (Zielona Góra: Faculty of Economics and Management Press)
Mobile phones have settled in our lives for good. The technological development made them actual miniature computers with significant computing capability and many diverse functions, which earned them the name "smartphones". They create new possibilities of application, also in business environments. As it turns out, already today smartphones are the most popular mobile devices used in supply chain management. Surely, as versatile and multi-functional devices, they will gain even larger share in the implementation of business tasks in the foreseeable future. The purpose of this paper is to describe the potential areas in supply chain management smartphones can be used in, compared to the current trends. The specified examples of application will be used to draw conclusions regarding the expected effects of use and most promising areas of implementation. These deliberations will be put in a wider social context, which is inevitable if we are to treat the consumer as the last link in the supply chain which, owing to the reported demand, is becoming a causative factor in all flows of goods.
Keywords: łańcuch dostaw; zarządzanie łańcuchem dostaw; smartfony; technologie mobilne; supply chain; supply chain management; smartphones; mobile technologies